PENGARUH MODEL KNISLEY BERBASIS MEAS TERHADAP PEMECAHAN MASALAH DAN NUMERASI SISWA DITINJAU DARI SELF-REGULATED LEARNING - Abi Fadila; Sofyatul Aulia; Bambang Sri Anggoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Knisley learning model based on Model Eliciting Activities (MEAs) on students’ problem-solving and numeracy skills, while also examining the contribution of Self-Regulated Learning (SRL) to these outcomes. The research employed a quantitative approach with a 2×3 factorial design under a quasi-experimental method. The sample consisted of 60 eighth-grade students divided into an experimental class (taught using the Knisley model with MEAs) and a control class (taught using conventional teacher-centered methods). Data were collected through problem-solving and numeracy tests, along with an SRL questionnaire. The results showed that the Knisley learning model with MEAs significantly improved students' problem-solving and numeracy abilities compared to conventional methods. The average posttest scores in the experimental group were 83.87 for problem-solving and 79.73 for numeracy, both higher than the control group. Additionally, students with high SRL levels performed better across both domains. However, no significant interaction effect was found between the learning model and SRL levels. These findings suggest that problem-based learning approaches such as MEAs and independent learning strategies like SRL contribute separately to improved student learning outcomes. The study recommends implementing contextual, activity-based learning models alongside SRL reinforcement to enhance mathematics instruction.